Prostatic artery embolization for treatment of lower urinary tract symptoms: a Markov model-based cost-effectiveness analysis : health services research and policy - Rink, Johann; Froelich, Matthias F.; McWilliams, Justin P.; Gratzke, Christian; Huber, Thomas; Gresser, Eva; Schönberg, Stefan; Diehl, Steffen J.; Nörenberg, Dominik (Journal of the American College of Radiology, 2022)
Purpose - The aim of this study was to investigate whether prostatic artery embolization (PAE) can be considered a long-term cost-effective treatment option in patients with lower urinary tract symptoms secondary to benign prostatic hyperplasia in comparison to transurethral resection of the prostate (TURP). - Methods - The in-hospital costs of PAE and TURP in the United States were obtained from a recent cost analysis. Clinical outcomes including nature and rate of adverse events for TURP and PAE along with rates of retreatment because of complications or clinical failure were obtained from peer-reviewed literature. A decision tree-based Markov model was created, analyzing long-term cost-effectiveness for TURP and PAE from a US health care sector perspective. Cost-effectiveness over a time frame of 5 years was estimated while assuming a willingness to pay of $50,000 per quality-adjusted life-year (QALY). The primary outcome was incremental cost-effectiveness ratio. - Results - PAE resulted in overall cost of $6,464.92 and an expected outcome of 4.566 QALYs. In comparison, TURP cost $9,221.09 and resulted in expected outcome of 4.577 QALYs per treatment. The incremental cost-effectiveness ratio for TURP was $247,732.65 per QALY. On the basis of the willingness-to-pay threshold, PAE is cost effective compared with TURP. - Conclusions - On the basis of our model, PAE in comparison with TURP can be regarded as a cost-effective treatment option for patients with lower urinary tract symptoms within the US health care system.
Online verfügbar: 25. April 2022, Artikelversion:16. Juni 2022
Gesehen am 06.02.2024